2005
DOI: 10.1002/ijc.20957
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutation associated with dysregulation of apoptosis in human colorectal neoplasms

Abstract: To understand the role of BRAF dysfunction in the carcinogenesis and progression/development of colorectal tumors, the authors investigated genetic alterations in the BRAF gene in human colorectal neoplasms as well as the effects of an RAS inhibitor in BRAF-mutant cells. Seven colon cancer cell lines and 116 colorectal tumors (34 adenomas and 82 adenocarcinomas) were analyzed. Genetic alterations in the BRAF and K-ras genes were examined using polymerase chain reaction-single strand conformation polymorphism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
3
33
0
1
Order By: Relevance
“…As for BRAF alone, as its activation is more prominent in early stages rather than in advanced stages of MSS CRC, we can hypothesize that BRAF activation alone is not sufficient to induce cancer progression in a high frequency of MSS CRC. Its activation in few advanced cases suggests that, in these CRCs, BRAF activation may contribute to tumour progression by protecting cells from apoptosis as suggested by Hingorani et al (2003) and Ikehara et al (2005).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…As for BRAF alone, as its activation is more prominent in early stages rather than in advanced stages of MSS CRC, we can hypothesize that BRAF activation alone is not sufficient to induce cancer progression in a high frequency of MSS CRC. Its activation in few advanced cases suggests that, in these CRCs, BRAF activation may contribute to tumour progression by protecting cells from apoptosis as suggested by Hingorani et al (2003) and Ikehara et al (2005).…”
mentioning
confidence: 80%
“…It was previously shown that KRAS activation occurs in the first steps of colorectal carcinoma progression, along the adenomacarcinoma sequence (Vogelstein et al, 1988;Fearon and Vogelstein, 1990). According to the literature, BRAF mutations were more frequently found in premalignant colon polyps and early rather than in advanced colorectal carcinomas (Rajagopalan et al, 2002;Yuen et al, 2002;Ikehara et al, 2005). Similar observations have been made in other tumour models, namely activating BRAF mutations have been detected in a high proportion of naevi and benign melanocytic skin lesions (Pollock et al, 2003;Yazdi et al, 2003), although in this specific model, activating mutations of BRAF have also been identified in approximately 90% of melanomas Kumar et al, 2003).…”
mentioning
confidence: 99%
“…The data show the mean 6 SD of three independent experiments. The KRAS mutation statuses of the CRC cell lines were obtained from a previous report 45 …”
Section: Growth-inhibitory Effect Of Cetuximab On Crc Cell Lines Withmentioning
confidence: 99%
“…4,5 The BRAF 600E mutant can replicate many of the effects of mutant RAS; indeed, expression of endogenous BRAF 600E promotes anchorage-independent growth, morphologic transformation, cell proliferation and cell survival in primary mouse embryo fibroblasts. [6][7][8][9][10][11] As the only physiologically defined substrate of RAF, MEK1/2 plays a key role in mediating the effects of RAS and RAF. 12,13 Since genetic inhibition of the ERK1/2 pathway reverses RAS and RAF transformation, and pharmacological inhibition of MEK1/2 is feasible, 14 this pathway has attracted much attention in the search for new chemotherapeutics and selective small molecule MEK1/2 inhibitors have been identified, including PD184352 (CI-1040), PD0325901 and AZD6244 (ARRY-142886).…”
Section: Uiccmentioning
confidence: 99%